Reaching Standards and Beyond in Kindergarten : Nurturing Children's Sense of Wonder and Joy in Learning. - Jacobs, Gera (SAGE Publications, 2009)
Help kindergarten students meet national standards in developmentally appropriate ways! This book shows teachers how to help young children reach standards in literacy, mathematics, science, social studies, and the arts through creative play activities that ignite their enthusiasm to learn. The authors also offer suggestions for promoting healthy physical and social-emotional development. This resource: Presents authentic assessments for measuring student progress toward standards Offers tips for working with English language learners and children with special needs Discusses how.